2023
DOI: 10.2106/jbjs.22.01088
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Radiographic and Pulmonary Function Outcomes After Dual Growing-Rod Treatment for Severe Early-Onset Scoliosis

Abstract: Background:We evaluated long-term outcomes (radiographic parameters and pulmonary function) at a minimum follow-up of 5 years after use of dual growing rods (DGRs) to treat severe early-onset scoliosis (sEOS).Methods:Among a total of 112 patients who were diagnosed with early-onset scoliosis (EOS) and were treated with DGRs between 2006 and 2015, 52 patients had sEOS, with a major Cobb angle of >80°. Of these patients, 39 with a minimum follow-up of 5 years had complete radiographic and pulmonary function test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The pulmonary function test in this case series showed that, as percentages of the predicted volume, the FEV1 was 71.61% and the forced vital capacity (FVC) was 69.88%, which indicated a relatively satisfactory result. In theory, pulmonary function is closely related to scoliosis correction and spinal height, as both affect lung volume 26 . A T1-T12 height of ≥18 cm may represent a threshold value for adequate forced vital capacity (>50% of predicted), and a T1-T12 height of ≥22 cm at skeletal maturity appears to allow nearly normal pulmonary function 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary function test in this case series showed that, as percentages of the predicted volume, the FEV1 was 71.61% and the forced vital capacity (FVC) was 69.88%, which indicated a relatively satisfactory result. In theory, pulmonary function is closely related to scoliosis correction and spinal height, as both affect lung volume 26 . A T1-T12 height of ≥18 cm may represent a threshold value for adequate forced vital capacity (>50% of predicted), and a T1-T12 height of ≥22 cm at skeletal maturity appears to allow nearly normal pulmonary function 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The researchers compared preoperative and postoperative parameters with those of healthy children and found decreased deviation from normality. Another study of 52 children with severe early-onset scoliosis found improved pulmonary function parameters >1 year following initial dual growing rod surgery 53 . Pulmonary function was not significantly different at 12 months after the surgical procedure, even though the spinal height had significantly improved in the first year, indicating that lung function may take longer to catch up with the change in thoracic volume.…”
Section: Early-onset Scoliosismentioning
confidence: 99%